al-Lughah al-‘Arabīyah wa-Jamālīyāt al-Īqā‘ - Mohammad Ali Ibnian; Mohammed Ali Reda Mallah (Al-Ma‘rifah, 2019)
The relationship between Arabic language and the musical rhythm is very strong, the language is an art pot of different colors and forms, the rhythm is closely related by the sense and the pronunciation, and it is the strength of poetry and the Base of systems. Singing has not found a place since the pre-Islamic era until the poetry emerged which was truly the Dīwān of Arabs. The art of singing has become more prevalent than other musical Arts in the Arab world. The songs were the first musical expressive tools that added to the melody of poetry more attractive and fun elements. So the study came to show the relationship between music and Arabic language in terms of structures, rules and construction, which are what they share together. The study also concerned about the importance of rhythm in the linguistic music structure.